SUPER MEANNESS OF INDEPENDENT AND SPECIAL CLASS OF GRAPH - Murugan, A. Nellai (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
In this paper, we prove thatTriangular Snake Tn ,Double Triangular Snake C2(Pn), Graph G = Cn@ Tm (n: odd), Graph G = Cn@ DTm , Graph G = i , Graph G = mPn, Graph G = nPnmPm, Graph G = TP(n), Graph G = DT(n) = [Pn : C32] and Graph G = SSL(n) are super mean graphs. Keywords: Super Mean Graph, Super Mean Labelling.